Match and Training Injuries Sustained by Professional Male Rugby Union Players in Scotland - Bailey, Stuart John; Martindale, Russell; Engebretsen, Lars; Robson, James Peter; Palmer, Debbie (International Journal of Sports Medicine, 2025)
Rugby union (‘rugby’) is a full-contact sport, with previous studies across the globe reporting a high incidence of injury. However, no injury surveillance study of professional male players in Scotland exists in contemporary literature. The current study therefore aimed to describe the incidence, severity, burden and nature of match and training injuries sustained by male professional club rugby players in Scotland. A prospective cohort study of injuries sustained during matches and training across the 2017/18 and 2018/19 seasons was undertaken, with injury and exposure definitions in line with the international consensus statements. Injury incidence was 136.2/1,000 player match hours and 4.1/1,000 player training hours, the median injury severity was 7.0 days (match) and 7.5 days (training) and injury burden was 2,887.0/1,000 player match hours and 102.3/1,000 player training hours. Concussion (match) and posterior thigh muscle injuries (training) were the most common specific diagnoses. Injury incidence in this population was higher than reported elsewhere in previous studies. However, high incidences of tackle injuries and concussion injuries agree with previous literature, reinforcing the need for mitigation strategies targeting these areas.
Keywords: Rugby; Epidemiology; Injury; Concussion; Player Welfare